2011
DOI: 10.1186/1742-6405-8-20
|View full text |Cite
|
Sign up to set email alerts
|

T cell Activation does not drive CD4 decline in longitudinally followed HIV-infected Elite Controllers

Abstract: BackgroundElite controllers (EC) are a rare subset of HIV infected individuals who control viral load below 50 copies/ml of plasma without treatment.MethodsThirty four EC were studied. The slope of CD4 count change was available for 25 of these subjects. We assessed immune activation by measuring the percent of CD38+HLA-DR+CD8+ T cells in the EC group and comparing it with that in 24 treatment-naïve HIV disease progressors and 13 HIV uninfected healthy controls.ResultsCompared to HIV uninfected subjects, EC ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…Elite controllers have been shown to have a greater magnitude of immune activation compared to those with suppressed viral load on ART [24]. Despite this finding, however, one study showed that T cell activation was not a driver of CD4 decline in elite controllers [26]. Since HIV is a chronic inflammatory disease, the development of a therapeutic vaccine that can reduce immune activation as well as reduce plasma viremia would be highly advantageous.…”
Section: Elite Controllers and Ltnp As Models For Functional Cure Of mentioning
confidence: 86%
“…Elite controllers have been shown to have a greater magnitude of immune activation compared to those with suppressed viral load on ART [24]. Despite this finding, however, one study showed that T cell activation was not a driver of CD4 decline in elite controllers [26]. Since HIV is a chronic inflammatory disease, the development of a therapeutic vaccine that can reduce immune activation as well as reduce plasma viremia would be highly advantageous.…”
Section: Elite Controllers and Ltnp As Models For Functional Cure Of mentioning
confidence: 86%
“…Tolerance to self and the state of activation of NK cells is determined by an ontogenic process known as education, which requires the interaction of inhibitory NK receptors (iNKRs) with their cognate HLA ligands on neighboring cells . Education is a complex process whereby functionality is tuned by the number of iNKRs engaged, the strength of interactions between iNKRs and their ligands and whether activating NK cell receptors (aNKRs) are also engaged . NK cells lacking iNKRs for self‐HLA ligands remain uneducated and hyporesponsive .…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of these patients, this spontaneous control of HIV-1 is associated with normal CD4 T cells, however, a small proportion of elite controllers develops declining number of CD4 T cells despite undetectable levels of HIV-1 viremia[1215]. Here, we comprehensively assessed naïve T cell subsets, thymic output and frequencies of recent thymic emigrants in a cohort of EC with normal or low CD4 T cell counts.…”
Section: Introductionmentioning
confidence: 99%